2014
DOI: 10.1134/s0965545x14040063
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of the heat-resistant polyimides ULTEM™ and EXTEM™ with the use of GROMOS53a6 and AMBER99 force fields

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…52,59,60,64 The simulation was performed in the NpT ensemble at a temperature of 600 K under a pressure of 1 bar. 52,59,60,64 The simulation was performed in the NpT ensemble at a temperature of 600 K under a pressure of 1 bar.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…52,59,60,64 The simulation was performed in the NpT ensemble at a temperature of 600 K under a pressure of 1 bar. 52,59,60,64 The simulation was performed in the NpT ensemble at a temperature of 600 K under a pressure of 1 bar.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…Test simulations showed that the use of the Nose-Hoover thermostat and the Parhinello-Rahman barostat do not lead to any significant changes in the discussed structural properties. 52,64 Ewald summation method (PME) 76 was used to account for the electrostatic interactions. 74 The values of the partial charges for the atoms of carboxyl groups attached to the CNT were taken as standard values for the Gromos53a5 force field 72 which was parameterized for simulating systems in the media with low permittivity.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect is explained by the formation of associates via electrostatic interactions between sulfur and oxygen atoms of the sulfone group [61]. Computer simulation experiments revealed that these interactions play an important role in the absence of such groups as well [69]. The transport characteristics of PIs were found to be affected by the presence of rigid or flexible frag ments.…”
Section: Polyimides and Polyamidesmentioning
confidence: 99%